2018
DOI: 10.3389/fpls.2018.00452
|View full text |Cite
|
Sign up to set email alerts
|

Heavy Metal Stress, Signaling, and Tolerance Due to Plant-Associated Microbes: An Overview

Abstract: Several anthropogenic activities including mining, modern agricultural practices, and industrialization have long-term detrimental effect on our environment. All these factors lead to increase in heavy metal concentration in soil, water, and air. Soil contamination with heavy metals cause several environmental problems and imparts toxic effect on plant as well as animals. In response to these adverse conditions, plants evolve complex molecular and physiological mechanisms for better adaptability, tolerance, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
139
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 364 publications
(141 citation statements)
references
References 145 publications
(145 reference statements)
2
139
0
Order By: Relevance
“…The microorganism resistance, refers to the ability to resist the effects of pollutants which are usually effective against them, while microorganism resistance, refers to the ability to adapt to persistent pollutants (Bhalerao, 2013). Tiwari and Lata (2018) suggest that tolerance and resistance to the toxic effects of heavy metals depend on the mechanisms involved. In short, tolerance to heavy metals can be defined as a phenomenon where resistance microorganisms increase to again heavy metal stress which can lead to poisoning.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The microorganism resistance, refers to the ability to resist the effects of pollutants which are usually effective against them, while microorganism resistance, refers to the ability to adapt to persistent pollutants (Bhalerao, 2013). Tiwari and Lata (2018) suggest that tolerance and resistance to the toxic effects of heavy metals depend on the mechanisms involved. In short, tolerance to heavy metals can be defined as a phenomenon where resistance microorganisms increase to again heavy metal stress which can lead to poisoning.…”
Section: Resultsmentioning
confidence: 99%
“…This perspective establishes that over time, in an ecosystem, exposure to heavy metal contamination increases tolerance to the community of microorganisms (Shade et al, 2012). Tiwari and Lata (2018) showing that long-term exposure heavy metals in puts pressure on soil microbes and increases tolerance. They concluded that the long-term accumulation of heavy metals in the soil gave the time to community of microorganisms to adapt to heavy metals.…”
Section: Introductionmentioning
confidence: 99%
“…An important characteristic of the α-proteobacteria is its genome plasticity that allows different genome rearrangements including deletions or duplications (14, 15). We made a phylogenetic analysis to get a wider view on the evolutionary relationship among the ADCs from α- and γ-proteobacteria This ML-based tree inferred from the α- and γ-proteobacteria ADCs is shown in fig.…”
Section: Resultsmentioning
confidence: 99%
“…These strategies evidently engender alterations to a number of morphological attributes of such plants. In addition, these responses have been shown to be species-specific with different plant species responding differently to even the same level of pollution (Shahid et al, 2015;Fashola et al, 2016;Tiwari and Lata, 2018). However, understanding the mechanism of the survival strategies or adaptive modifications of these plants in response to heavy metal pollution is ver y cr ucial.…”
Section: Discussionmentioning
confidence: 99%
“…Pollution from metal mining is one of the most serious environmental problems in our contemporary environment (Singh et al, 2011;Chen et al, 2018). Generally, mine tailings are a major source of contaminants of heavy metals in water, soil and biota (Nwuche and Ugoji, 2008;Tiwari and Lata, 2018). Also, soil contamination with heavy metals may cause changes in the composition of soil microbial community, thereby adversely altering soil characteristics (Kurek and Bollag, 2004;Fashola et al, 2016).…”
Section: Introductionmentioning
confidence: 99%